MARC 1.0: apps to integrate culture the fun way in a university orientation programme / Sheela Paramasivam … [et al.] - Paramasivam, Sheela; Adnan Johan @ Eddy Luaran, Afni Anida; Jamil, Nur Fatima Aisyah; Ganesan, Asha (Faculty of Computer and Mathematical Sciences, 2022)
The Covid-19 Pandemic has caused instructors worldwide to make the switch from the traditional face to face teaching to online platforms, which not only affected the teaching of content courses in institutions of higher learning but also general programmes such as orientations programmes for foreign students who are unable to enroll in the study programmes in the host country of their choice. Travel restrictions due to the pandemic has forced orientation programmes to be minimised or done without. This leaves a void in the students having to cope, understand or adapt to the culture of the host country in which they pursue their studies. This paper looks at effectiveness of using MARC (Malaysian Religion and Customs), an online quizizz game apps as an extension to the teaching and learning of culture and customs in a virtual teaching module: ‘Malaysia and Culture’ for a group of students from a university in China pursuing a short course via online distance learning in Malaysia. After the teaching and learning of the Malaysian culture module, the China students were exposed to MARC to reinforce their learning and understanding of Malaysian religion and culture. Results of a survey gauging the effectiveness of MARC revealed that it is an effective and fun avenue and platform for orientating foreign students from China to gain insights into the religion, customs, and culture in Malaysia. The inclusion of attractive visuals, a timer, correct answers as well as scores obtained using MARC motivated the Chinese students to understand, learn and gain insights to the culture of Malaysia in a fun and engaging way. Additionally, MARC could be installed in their handphones for convenience. In short, MARC is a novel way of using games in a fun and interactive manner to introduce the culture of Malaysia to any foreign or local students pursuing their studies. MARC can be further explored and extended to include other aspects of Malaysian culture such as food, festivals, traditional songs, clothes and even taboos to tourists visiting Malaysia in the hope of introducing Malaysia as a land of beauty and diversity.